Comparative Proteomic Analysis of Different Isolates of Fusarium oxysporum f.sp. lycopersici to Exploit the Differentially Expressed Proteins Responsible for Virulence on Tomato Plants - Manikandan, Rajendran; Harish, Sankarasubramanian; Karthikeyan, Gandhi; Raguchander, Thiruvengadam (Frontiers in Microbiology, 2018)
The vascular wilt of tomato caused by Fusarium oxysporum f.sp. lycopersici is an important soil borne pathogen causes severe yield loss. The molecular characterization and their interaction with its host is necessary to develop a protection strategy. Twenty isolates of Fusarium oxysporum f.sp. lycopersici (FOL) were isolated from wilt infected tomato plants across Tamil Nadu. They were subjected to cultural, morphological, molecular and virulence studies. The results revealed that all the isolates produced both micro and macro conidia with different size, number of cells. The colors of the culture and growth pattern were also varied. In addition, chlamydospores were observed terminally and intercalary. The PCR analysis with Fusarium oxysporum species-specific primer significantly amplified an amplicon of 600 bp fragment in all the isolates. Based on the above characters and pathogenicity, isolate FOL-8 was considered as virulent and FOL-20 was considered as least virulent. Proteomics strategy was adopted to determine the virulence factors between the isolates of FOL-8 and FOL-20. The 2D analyses have showed the differential expression of 17 different proteins. Among them, three proteins were down regulated and fourteen proteins were significantly up regulated in FOL-8 than FOL-20 isolate. Among the 17 proteins, ten distinct spots were analysed by MALDI-TOF. The functions of the analysed proteins, suggested that they were involved in pathogenicity, symptom expression and disease development, sporulation, growth and higher penetration rate on tomato root tissue. Overall, these experiments proves the role of proteome in pathogenicity of Fusarium oxysporum f.sp. lycopersici in tomato and unravels the mechanism behinds the virulence of the pathogen in causing wilt disease.